Efficient Test Methodologies for High-Speed Serial Links - Hong, Dongwoo; Cheng, Kwang-Ting.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
With the increasing demand for higher data bandwidth, communication systems$1 (Bdata rates have reached the multi-gigahertz range and even beyond. Advances in semiconductor technologies have accelerated the adoption of high-speed serial interfaces, such as PCI-Express, Serial-ATA, and XAUI, in order to mitigate the high pin-count and the data-channel skewing problems. However, with the increasing number of I/O pins and greater data rates, significant challenges arise for testing high-speed interfaces in terms of test cost and quality, especially in high volume manufacturing (HVM) environments. Efficient Test Methodologies for High-Speed Serial Links describes in detail several new and promising techniques for cost-effectively testing high-speed interfaces with a high test coverage. One primary focus of Efficient Test Methodologies for High-Speed Serial Links is on efficient testing methods for jitter and bit-error-rate (BER), which are widely used for quantifying the quality of a communication system. Various analysis as well as experimental results are presented to demonstrate the validity of the presented techniques.s
An Efficient Jitter Measurement Technique -- BER Estimation for Linear Clock and Data Recovery Circuit -- BER Estimation for Non-linear Clock and Data Recovery Circuit -- Gaps in Timing Margining Test -- An Accurate Jitter Estimation Technique -- A Two-Tone Test Method for Continuous-Time Adaptive Equalizers -- Conclusions.
Keywords: Computer science; Microprocessors; Computer engineering; Electronic circuits; Computer Science; Computer Engineering; Circuits and Systems; Register-Transfer-Level Implementation; Electronic books